PERAN PEMASARAN DIGITAL: SEBUAH PERSPEKTIF DARI MANAJER HOTEL DI SUMBAWA - Tomy Dwi Cahyono; Reza Muhammad Rizqi (Jurnal Bina Manajemen, 2022)
The role of the Internet in the buying behavior of tourists has led to a change in increasingly digital marketing plans. This study aims to find out how hotel industry managers use digital marketing as a marketing tool. In this study, using qualitative methodologies was adopted. Then semi-structured interviews were conducted with managers and marketers from 39 hotels that participated in the study. Digital marketing tools provide many benefits to the hospitality industry. However, managers still haven't used their potential in the realm of digital marketing. Although the data was collected at the end of 2020, we believe that the findings and recommendations are still valid and relevant. This study offers several recommendations to improve the effectiveness of hotel digital marketing in Sumbawa. Although it uses a thematic approach, this article provides an extensive assessment of the range of digital marketing communications in the luxury segment of the hospitality industry. In addition, these estimates are made for all units on a municipal scale.